(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2004)
The text is based on two articles dealing with psychotherapy research – how existential therapists interact with research issues (Cooper, 2004; Mahrer and Boulet; 2004). Some of the topics introduced by the authors are reviewed and a number of reasons are then presented to show the importance of research on psychotherapy, independent of the theoretical framework of the therapist. Besides, these push factors were examined by leading researchers in the field of existential phenomenology and the question is still a moot point among major academics. It is argued that existential therapists may play an important and unlimited role in psychotherapy research.